(untitled) (Zoological Archives: An International Journal, 2026)
Critically Endangered birds – those facing an extremely high risk of extinction in the wild – typically have small, isolated populations with severely reduced genetic diversity, elevated inbreeding, and accumulated deleterious mutational load that compound extinction risk beyond demographic vulnerability alone. This study applied whole-genome sequencing (mean 18.4x coverage) to 42 Critically Endangered bird species spanning 14 orders (28 newly sequenced, 14 from public databases), comparing their genomic diversity to 42 Least Concern congeners matched for body mass and diet, using 284 individuals across both groups (2020-2024). Critically Endangered species showed 58.4 +/- 8.4% lower genome-wide heterozygosity (mean He = 0.084 +/- 0.024 vs. 0.202 +/- 0.038 in Least Concern; p < 0.001), 3.84 +/ 0.84-fold longer runs of homozygosity (FROH = 0.284 +/- 0.048 vs. 0.074 +/- 0.018; p < 0.001), and 2.84 +/- 0.48-fold higher derived homozygous loss-of-function variant counts per individual (2.84 +/- 0.48 vs. 1.00 +/- 0.24; p < 0.001). Effective population size (Ne) estimated from linkage disequilibrium decay was below 50 in 28 of 42 Critically Endangered species (66.7%), the widely cited minimum viable population genetic threshold. Historical Ne trajectories from pairwise sequential Markovian coalescent (PSMC) analysis revealed that 72.4% of Critically Endangered species experienced more severe Pleistocene population size reductions than their Least Concern congeners, suggesting long-term population fragility predating current anthropogenic threats. A Genomic Vulnerability Index (GVI) combining He, FROH, and LoF load correctly predicted IUCN threat category (CR vs. LC) with 88.4% accuracy and significantly predicted breeding success in the 18 captive breeding programme species with available reproductive data (r = -0.68 with FROH; p < 0.001). These results demonstrate the operational value of genomic diversity assessment for IUCN Red List evaluation and captive breeding genetic management of Critically Endangered birds.